2009
DOI: 10.1016/j.bbamem.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Membrane hydration correlates to cellular biophysics during freezing in mammalian cells

Abstract: Cell survival during freezing applications in biomedicine is highly correlated to the temperature history and its dependent cellular biophysical events of dehydration and intracellular ice formation (IIF). Although cell membranes are known to play a significant role in cell injury, a clear correlation between the membrane state and the surrounding intracellular and extracellular water is still lacking. We previously showed that lipid hydration in LNCaP tumor cells is related to cellular dehydration. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 33 publications
0
31
1
1
Order By: Relevance
“…In particular, in samples with controlled ice nucleation the calculated diffusion distance within the freeze concentrated matrix is significantly larger than that following spontaneous ice nucleation. 13 Effects on cell dehydration of controlled and spontaneous ice nucleation have previously been confirmed using Fourier transform infrared spectroscopy of mammalian cell lines 23,24 and horse spermatozoa 25 and it has been shown that cell dehydration is required to avoid lethal intracellular ice formation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in samples with controlled ice nucleation the calculated diffusion distance within the freeze concentrated matrix is significantly larger than that following spontaneous ice nucleation. 13 Effects on cell dehydration of controlled and spontaneous ice nucleation have previously been confirmed using Fourier transform infrared spectroscopy of mammalian cell lines 23,24 and horse spermatozoa 25 and it has been shown that cell dehydration is required to avoid lethal intracellular ice formation.…”
Section: Discussionmentioning
confidence: 99%
“…the ability of different organisms to survive even complete dehydration. This gives many potential applications, such as tailored cryosurgery in medicine (Balasubramanian et al, 2009), but also in biopreservation, i.e. the storage of biological material (Aksan et al, 2009;Franca et al, 2007), even in the scope of space projects (Ricci et al, 2005;Rothschild and Mancinelli, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…10 One particularly fascinating aspect of lipid behavior is the effect that hydration has on lipid function. [11][12][13] For instance, in the stratum corneum, it is important to regulate hydration such that the skin can act as an effective barrier. [14][15][16][17] The importance of hydration is highlighted by the fact that when cells become dehydrated, they modify their membrane composition to retain suitable fluidity.…”
Section: Introductionmentioning
confidence: 99%